Diversification of inflorescence development in The PCK clade (Poaceae: Panicoideae: Paniceae) - Reinheimer, Renata (2009)
In grasses, inflorescence diversification and its correlation with species evolution are intriguing and not well understood. Part of this problem lies in our lack of comprehension about the inflorescence morphological complexity of grasses. We focused our study on the PCK clade (named for phosphoenol pyruvate carboxykinase), a well‐supported monophyletic group for which the relationships among its taxa are not well resolved. Interestingly, the PCK clade has an extensive diversity of adult inflorescence forms. A comparative developmental approach can help us to understand the basis of such morphological differences as well as provide characters that can be used in phylogenetic studies of the group. Using SEM studies, we demonstrate that inflorescence morphology in this clade is even more complex than what is typically observed in adult forms. We describe a number of new characters, and some classical features previously used for taxonomic purposes are redefined on the basis of development. We also define four morphological groups combining adult inflorescence form and development, and we discuss some of the evolutionary aspects of inflorescence diversification in the PCK clade. Taxonomic delimitation among genera in the PCK clade remains confusing and unclear where molecular and morphological studies support different classifications.